The micronutrient status of long-term Home Enteral Nutrition (HEN) patients of Te Whatu Ora Counties Manukau : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Mantovani, Marcos (Massey University, 2023)
Background: Iron, folate, vitamin B₁₂, copper, and zinc are essential nutrients that play a role in metabolic processes associated with disease prevention and improving health complications and well-being. Enteral feeds contain adequate nutrients that patients may require. However, these nutrients may be digested and absorbed differently than in whole foods. Nutrient deficiencies can only be treated once recognised and confirmed, so it is in our best interest to know if deficiency is present in patients receiving long-term home enteral nutrition (HEN). Aim: To investigate the nutritional status of long-term enterally fed patients over 18 years of age in Te Whatu Ora Counties Manukau. Methods: Data from 42 patients receiving long-term enteral nutrition for ≥ 4 weeks were collected. The blood concentrations of iron, copper, zinc, folate and vitamin B₁₂ of only 21 participants were obtained and compared to recognised cut-offs for adults. For all participants, a detailed 5 x 24-hour recall of dietary intake, including enteral nutrition (EN) and oral food sources, was determined and compared to the Recommended Daily Intake (RDI) for age appropriate. A physical assessment of nutritional signs and symptoms determined the presence of deficiency for the selected micronutrients. The Charlson comorbidity index score (CCIS) was evaluated and categorised by summing the weight of 17 comorbidities, severe (>5), moderate (3-4), mild (1-2), or no comorbidities (0), indicating the degree of mortality within the next 10-years. Descriptive statistical analyses were completed for participants' characteristics, demographics, and health characteristics by gender. Generalised linear models and binary regression estimated the association between dietary intake, biomarker status and physical signs and symptoms of deficiency. A stepwise regression method was performed on the model residuals to confirm normality (histogram and Shapiro-Wilk), independence (Durbin-Watson), equality of variance (scatter plot) and multi-collinearity (VIF and tolerance). Results: The rates of total participants with blood results lower than the reference ranges for iron and zinc were 19.04% (n=4) and 66.7% (n=14), respectively. Folate, vitamin B₁₂ and copper were all within their respective reference ranges. Dietary intake for women only was below the RDIs for iron (n=9, 47%), dietary folate equivalent (DFE) (n=3, 15.9%), vitamin B₁₂ (n=3, 26%), zinc (n=1, 5.3%), and copper (n=1, 6.3%). Most participants had adequate dietary intake via EN feeds, excluding iron, with a mean±standard deviation of 17.1±8.3 mg/d (RDI <18mg/d for women). Alopecia was correlated with decreased dietary intake of iron and zinc and reduced serum zinc concentrations. The presence of eczema, dermatitis and perioral stomatitis and the absence of wound healing and alopecia combined were associated with lower blood zinc concentration. Increased age, cerebrovascular accident (CVA) & transient ischemic attack (TIA), liver disease, solid tumour and myocardial infarction were contributor comorbidities found to decrease the risk of 10-year survival rates among the participants. Conclusion: Blood results below the reference range values for iron and zinc were significant. Given that the total dietary intake for iron and zinc was insufficient to meet the RDIs for women, it may suggest that dietary iron and zinc are lacking in the diets of HEN women patients. Strategies to improve this, including fortification and supplementations, may positively impact the nutritional status of HEN patients and should be investigated further. The physical signs and symptoms of deficiency were largely unrelated to their biomarker status and dietary intake; however, it is essential to regularly monitor the nutrition physical examination of HEN patients to detect any clinical symptoms of nutrient-related deficiencies.
Keywords: 321001 Clinical nutrition